Remediation quantum of organic amendments to immobilize potentially toxic heavy metals in wastewater-contaminated soils through maize cultivation - Zeeshan Manzoor, Muhammad; Sarwar, Ghulam; Ibrahim, Muhammad; Rehan, Saman Safdar; Hasnain, Zuhair; Rais, Afroz; Gul, Safia; Alfagham, Alanoud T.; Manono, Bonface O.; Mehmood, Kashf; Khan, Shahbaz (Frontiers in Environmental Science, 2024)
Wastewater is considered a good reservoir of mineral elements that can be used for agriculture, aquaculture, and some other activities after adopting suitable measures. The gap between supply and demand for water is increasing exponentially because of an abrupt boost in the world population. It is time to refocus attention on a kind of circulating water by reusing municipal wastewater for agricultural purposes, particularly irrigation. The recycled or treated water would be used as an alternative to fresh water. In a current study, the impact of various organic amendments was studied to mitigate the toxic effects of pollutants present in wastewater by cultivating maize as a test crop. In this experiment, treatments included T1 (Treatment 1) = control (wastewater polluted soil without application of any amendment), T2 = farmyard manure (FYM) at 2.5 tons ha -1 (hectare -1 ), T3 = FYM at 5.0 tons ha -1 , T4 = compost at 2.5 tons ha -1 and T5 = compost at 5.0 tons ha -1 . Application of FYM at 5.0 tons ha -1 (T3) was recorded as most effective, as maximum improvement was observed in soil characteristics pH, electrical conductivity (EC), sodium adsorption ratio (SAR), and organic matter. Treatment T3 remained most superior in reducing the concentration of heavy metals in soil, for example, lead, cadmium, nickel, and arsenic for T3 were 8.64, 1.34, 10.44, and 2.25 mg kg -1 (milligram per kg), respectively. Maximum fresh biomass (fodder yield) of 9.98 tons ha -1 was harvested when FYM was applied at 5.0 tons ha -1 to the soil as compared to 6.2 tons ha -1 from the control plot. The highest contents of nitrogen (1.20%), phosphorus (0.41%) and potassium (3.97%) were observed in maize plants for T3. In maize plants T3, the concentration of lead, cadmium, nickel, and arsenic was reduced to the levels of 1.92, 0.23, 2.28, and 1.25 mg kg -1 respectively. Therefore, it can be concluded from the findings of the experiment that the application of FYM significantly reduced heavy metal concentrations and improved soil health, along with maize crop growth and productivity.